I am going to show a proof of \[\sum_{n\geq 1}\dfrac{\Lambda(n)}{n^s}=-\dfrac{\zeta'(s)}{\zeta(s)}\] We start off by writing this as \[\sum_{p=prime}\sum_{k=1}^\infty \dfrac{\ln(p)}{p^{sk}}=\sum_{p=prime} \dfrac{\ln(p)}{p^s-1}\] Let this be; we will use this later.

Lemma: \(\sum_{n≥1} \dfrac{F(n)}{n^s}=\zeta(s)\sum_{p=prime}\dfrac{F(p)}{p^s-1}\) where F(n) is a completely additive function.

Proof: we can split the sum over primes. \(F(p^k)=kF(p)\). we use this and get \[\large\sum_{p=prime}\sum_{k=0}^\infty \dfrac{F(p^k)}{p^{sk}}\left(\sum_{p\not\mid n} \dfrac{1}{n^s}\right)=\sum_{p=prime}\sum_{k=0}^\infty \dfrac{kF(p)}{p^{sk}}\left(\zeta(s)-\zeta(s)p^{-s}\right)\\=\sum_{p=prime}F(p)\zeta(s)(1-p^{-s})\sum_{k=0}^\infty\dfrac{k}{p^{sk}}= \zeta(s)\sum_{p=prime}\dfrac{F(p)}{p^s-1}\]

Now \(\ln(n)\) is a completely additive function, so \[\sum_{n=1}^\infty \dfrac{\ln(n)}{n^s}=\zeta(s)\sum_{p=prime}\dfrac{\ln(p)}{p^s-1}\] We know that \(-\zeta'(s)=\sum_{n=1}^\infty \dfrac{\ln(n)}{n^s}\) and putting in the RHS's summation in terms of Von Mangoldt: \[\sum_{n=1}^\infty \dfrac{\Lambda(n)}{n^s}=-\dfrac{\zeta'(s)}{\zeta(s)}\]

## Comments

Sort by:

TopNewestI have changed a typo: From "completely multiplicative function" to "completely additive function" (regarding ln(n))

Other than that, great proof!

Extra: Alternative proof of lemma:

\[n=\prod _{p_j|n}^{ }p_j^{w_j}\]

\[F(n)=\sum _j^{ }w_jF\left(p_j\right)=\sum _{p^k|n}^{ }F\left(p\right)=1*f(n)P(n)\]

Where f(n) satisfies f(p^k)=F(p) and P(n) is 1 if n=p^k and is 0 otherwise. – Julian Poon · 9 months ago

Log in to reply